DESIGN AND ANALYSIS OF PIPELINE POST TRENCHING USING FINITE ELEMENT METHOD - Puteri Santosa, Lita
The subsea pipelines play a crucial role in transmitting energy resources such as oil and gas. To enhance the transportation capacity of oil and gas, the construction of subsea pipeline in Balikpapan is planned. Due to the congested maritime traffic conditions, the construction of subsea pipeline in Balikpapan considering the Minister of Transportation Regulation No. 129 of 2016 regarding Shipping Routes at Sea and Buildings and/or Installations in Waters, which emphasizes the need for pipeline trenching to avoid the risk of heavy objects collision. In planning the construction of this transmission pipeline, an analysis of the pipeline wall thickness is conducted using the design standards DNV ST F101, API RP 1111, and ASME B31.4, which satisfy the criteria of pressure containment, system collapse, propagation buckling, and combined loading. Subsequently, a stability analysis of the pipeline based on DNV RP F109 is performed to determine the required thickness of the concrete coating, also ensuring the stability of the pipeline under vertical and lateral loading. In the final stage, a post trenching pipeline modeling is conducted, encompassing the pipeline and seabed, to assess the stress distribution along the pipeline caused by post trenching. Based on the design and analysis process, the chosen wall thickness for a 20 inch (508 mm) diameter pipeline is 0.625 inches (15.875 mm), the concrete coating thickness is 1.929 inch (49 mm), and the maximum stress along the pipeline is found to be 281.505 MPa.